Design and Build Educational Game "New Normal" - Felicia Kusuma; Ridwan Sanjaya; Erdhi Widyarto Nugroho (SISFORMA, 2021)
Indonesia’s first confirmed case of COVID-19 infection was in early March 2020. Of course, the citizens in Indonesia want this pandemic to end soon. The fact is, there are plenty of people who do not apply the health protocols properly in daily life. Therefore, the effort to formulate the educational media in the form of a game will be carried out in this study. “New Normal” game is an educational media about how to apply the health protocols properly that have a nice user interface design so that the players will not get bored easily while playing. Thus, the knowledge about the importance of applying the health protocols properly will be embedded in every player’s mind.